PENGEMBANGAN POJOK BACA DESA JUNGKARE UNTUK MENINGKATKAN KETERAMPILAN LITERASI BACA TULIS DAN SAINS PADA ANAK - Hutomo, Suryo Priyo; Cahyaningrum, Ana Octavia; Diniyati, Deni; Triyaningsih, Nanda; Trijayanti, Patma; Rahmawati, Rani; Lestari, Resti Madiana; Amanah, Salimatul; Rukmana, Sandy Puspita; Yanti, Ulfah Aulia Dewi; Damayanti, Viki; Kusumawati, Woro Sophia Amirul; Firmansah, Fery (LPPM Universitas Widya Dharma Klaten, 2025)
The purpose of this service is to improve children's reading literacy, writing literacy, and science literacy skills through the development of a reading corner. The object of service is the children of Jungkare village, Karanganom sub-district, Klaten district. Reading literacy and writing literacy activities are wall magazine making while science literacy is in the form of simple rotary ice cream making activities. The service methods used are presentation, discussion, and practice. The activity stages consisted of socialization of the implementation and project exhibition. The results showed that the children of Jungkare village were very enthusiastic in participating in reading literacy, writing literacy, and science literacy activities.